Efektivitas Biolarvasida Kombinasi Ekstrak Daun Sirsak (Annona muricata) dan Bunga Marigold (Tagetes erecta L.) sebagai Pembasmi Jentik Nyamuk - Yuniar Trisna Wardana; Aminah Asngad (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to determine the effectiveness of using a biolarvicide combination of soursop leaf extract and marigold flowers as an exterminator for mosquito larvae. This research included a laboratory experiment using a completely randomized 2 factorial design. The first factor is a combination of soursop leaf extract and marigold flowers, namely, a) 75%:25% (F1); b) 50%:50% (F2); c) 25%:75% (F3). The second factor is the treatment dose, namely, a) 1% (D1); b) 2% (D2); c) 2.5% (D3). Each factor was repeated 3 times. Data analysis uses a non-parametric test, namely Kruskal-Wallist. The results of the study showed that the soursop leaf and marigold flower extract formula 75%:25% was most effective against mosquito larvae mortality at a dose of 2.5% within an observation period of 6 hours. In conclusion, soursop leaf and marigold flower extracts are effective mosquito larva repellents. Keywords: Biolarvicide, Marigold Flowers, Soursop Leaves, Effectiveness, Mosquito Larvae